A Novel ELISA Assay for the Detection of Anti-Prothrombin Antibodies in Antiphospholipid Syndrome Patients at High Risk of Thrombosis - Chinnaraj, Mathivanan; Pengo, Vittorio; Pozzi, Nicola (Frontiers in Immunology, 2021)
Autoantibodies targeting prothrombin (aPT) can be found in antiphospholipid syndrome (APS) patients. However, their detection has proven difficult to standardize. Here, we developed a new ELISA assay to improve the identification of aPT and compared its performance with currently available anti-phosphatidylserine/prothrombin antibodies (aPS/PT) and autoantibodies targeting prothrombin bound to the plastic plate (aPT-A) assays using a cohort of 27 APS patients at high risk of thrombosis. We generated a novel prothrombin variant, ProTS525A-Biot, carrying an artificial tag at the C-terminus suitable for site-specific biotinylation and added the mutation S525A to improve stability. ProTS525A-Biot was immobilized to neutravidin-coated plates at the desired density and with a defined orientation, i.e., pointing the N-terminal fragment-1 toward the solvent. Antibodies against ProTS525A-Biot (aPT-Bio) were found in 24 out of 27 triple-positive APS patients (88%). When compared to aPS/PT and aPT-A, aPT-Bio showed an excellent linear correlation with aPS/PT (R2=0.85) but not with aPT-A (R2=0.40). Since aPS/PT but not aPT-A are an emerging biomarker of thrombosis in APS, this method may find utility for detecting pathogenic aPT in APS but also other prothrombotic conditions such as COVID-19.